The ecology of dropouts in Torres High School - Espino, Iluminada (Galang) 1932- (s.n.], 1971)
The writer has chosen to delve into the problems of out-of-school youth as it affects and threatens our way of life. The study has attempted to get the ecology of drop-outs and its relevance to manpower development planning.